2008
DOI: 10.1002/biof.5520330105
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile lowering effect of SoyproTM fermented with lactic acid bacteria isolated from Kimchi in high‐fat diet‐induced obese rats

Abstract: Lactic acid bacteria are known to exert various physiologic functions in humans. In the current study, we investigated the effects of Soypro, a new soymilk fermented with lactic acid bacteria, like Leuconostoc kimchii, Leuconostoc citreum, and Lactobacillus plantarum, isolated from Kimchi, on adipocyte differentiation in preadipocyte 3T3-L1 cell lines and weight gain or the plasma lipid profile in Sprague-Dawley rats. Adipocyte 3T3-L1 cells treated with Soypro (10 microg/ml) significantly reduced the contents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Chronic high fat and fructose consumption, in terms of increased energy intake, has been shown a greater increase in bodyweights [23, 24]. Enhanced fat deposition with high fat-fructose diet may result in weight gain over a period of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic high fat and fructose consumption, in terms of increased energy intake, has been shown a greater increase in bodyweights [23, 24]. Enhanced fat deposition with high fat-fructose diet may result in weight gain over a period of time.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, controlled bodyweight by L. plantarum K68, FVF, and MIX supplements implies the reduced risk of CVD. Soypro, a fermented soymilk with lactic acid bacteria, isolated from Kimchi, was showed to inhibit the expression of transcription factors of adipocyte differentiation [23]. Yadav and colleagues [12] showed that dahi (curd), which contained lactobacillus bacteria prevent the bodyweight gain against high fructose diet.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reasonable to articulate that GLAB acts directly on PPAR γ and C/EBP α . Kim et al (2008) showed that treating 3T3-L1 cells with milk fermented with lactic acid bacteria isolated from kimchi decreased the levels of PPAR γ and C/EBP- α expression [28]. Thus, it could be possible that lactic acid bacteria isolated from gajami sik-hae affects the downstream genes of PPAR γ and C/EBP α , thus inhibiting adipogenesis in 3T3-L1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The fermented soymilk significantly decreased plasma LDL cholesterol in HFD-induced obesity in SD rats. 98 Sousa et al 99 reported that administration of Lactobacillus supernatants (LS) into the brains of rats resulted in weight loss without a decrease in food consumption, but with simultaneous increases of leptin expression in neurons and peripheral adipose tissue. LS also modulated the expression or release of other peptides involved in metabolism and body weight control.…”
Section: Antiobesity Effect Of Kimchi Labmentioning
confidence: 98%